Predicting the stability of early employment with its timing and childhood social and health-related predictors: a mixture Markov model approach - Helske Satu; Keski-Säntti Markus; Kivelä Juha; Juutinen Aapo; Kääriälä Antti; Gissler Mika; Merikukka Marko; Lallukka Tea (Bristol University Press, 2025)
To extend work careers, it is important to focus on all working-aged people including young adults. The aim of this study was to identify typical patterns of work participation among young adults after their first entry into the labour market and to examine whether the timing of entry together with parental and own socio-economic position and health predict early work participation. More in-depth understanding of early careers and their early determinants is important to plan targeted interventions and to promote more stable work participation among young adults. We used the Finnish Birth Cohort 1987 including data from several registers from all 59,476 children born in 1987 as well as their parents, followed until 2015. We estimated a mixture Markov model that allowed for joint identification of latent classes of labour-market attachment, estimation of labour-market transitions within classes, and prediction of class membership using childhood social and health-related determinants. We observed that the first entry into the labour market as measured by six months in continuous employment was not a permanent entry for many, not only due to negative reasons such as unemployment and ill health but also due to more voluntary reasons such as studies. Individuals entering the labour market at a later age were more likely to be in continuous employment thereafter. More advantaged background predicted exits due to studies or - when following a late entry - stable employment, while disadvantaged background factors predicted more unstable work and long-term exits from the labour market.